Validity of Canvaflipedia: E-Encyclopedia of Morphological Pteridophyta Diversity Based on Local Potential in Problem-based Learning - Yudhistian, Yudhistian; Wulandari, Tabitha Sri Hartati (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The need for e-encyclopedia development due to the low utilization of ICT in developing e-encyclopedias makes students lazy and less interested in studying the morphological diversity of Pteridophyta based on local potential. Therefore, the development of Canvaflipedia addresses the above problems as a learning medium that is more interactive and easily accessible to students, and can be applied in the PBL model of learning. This study aims to design and test the validity of an electronic encyclopedia related to the morphological diversity of Pteridophyta based on local potential in PBL learning. Methods: The type of research used is an R&D study with a 4D (Define, Design, Develop, and Disseminate) model, but the research only reached the development stage, which focused on validity testing by three validators using a validation sheet as a research instrument. Data was collected by compiling the results of the validation sheet and analyzed descriptively and quantitatively to interpret the validity results obtained. Results: The findings of the material expert validation test analysis showed a very valid category with an average value of 91.11%. By contrast, the results of the media expert validation test analysis showed a very valid category with an average value of 87.70%. Conclusions: Based on these results, the Canvaflipedia developed is very valid for application in PBL learning.